Perancangan Interface Aplikasi Pengaduan Masyarakat Kepada Kepolisian - Alkaf, Said Ammar; Basrul, Basrul; Mursyidin, Mursyidin (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Based on the results of the analysis conducted by the researchers, there are many unpredictable things like traffic accidents, robbery, theft case and others. This study aims to facilitate the community in reporting the unexpected events of each individual. The designed app will later give you an idea of which system will be used by the community to report instances that are experienced easily and quickly. This research uses prototyping method. This research is done by collecting the data needed to create an application design that can be used to disrupt the application. Data obtained for further processing can be obtained so that a design can be used as a picture when the application will be implemented.